The Spanish Pacific, 1521-1815
1 online resource (268 pages)
Keywords: The Spanish Pacific designates the space Spain colonized or aspired to rule in Asia between 1521 - with the arrival of Ferdinand Magellan - and 1815 - the end of the Manila-Acapulco galleon trade route. It encompasses what we identify today as the Philippines and the Marianas, but also Spanish America, China, Japan, and other parts of Asia that in the Spanish imagination were extensions of its Latin American colonies. This reader provides a selection of documents relevant to the encounters and entanglements that arose in the Spanish Pacific among Europeans, Spanish Americans, and Asians while highlighting the role of natives, mestizos, and women. A-first-of-its-kind, each of the documents in this collection was selected, translated into English, and edited by a different scholar in the field of early modern Spanish Pacific studies, who also provided commentary and bibliography.